Extraction socket preservation using a collagen plug combined withplatelet-rich plasma (PRP): A comparative clinico-radiographic study - Numaan Nisar; Kumar Nilesh; Mushtaq Ishaq Parkar; Prashant Punde (Tabriz University of Medical Sciences, 2020)
Background. Alveolar bone remodeling after tooth loss results in reduced ridge dimensions in horizontaland vertical planes. To prevent this, various authors have proposed different ridge preservationtechniques. A collagen plug is a novel material that has shown promising results in preserving thealveolar bone. PRP has also yielded favorable outcomes in wound healing and promoted osteoinductionand osteoconduction Methods. Thirty patients of both sexes with an age range of 30-18 years requiring bilateral extractionof teeth with similar tooth root anatomy in the maxilla or mandible were included in the study. Theextraction of teeth was carried out atraumatically. The patients' arches were randomly divided andlabeled as the test or control sides. Bone width was measured on both sides. A collagen plug, with PRP,was placed, and the extraction socket was sutured on the test side. The control side was just sutured. Abaseline RVG was taken to record the apico-coronal height. The patients were recalled after 10 days forsuture removal and evaluation of wound healing. Parameters were re-evaluated at three and six monthspostoperatively. The data were subjected to t-test and one-way ANOVA. Results. The height of the crestal bone on the grafted side was more when compared to the non-graftedside three and six months after tooth extractions, and the difference was statically significant (P<0.001).No statistically significant difference was seen in the width of the alveolar bone three and six monthsafter tooth extraction (P>0.05). Conclusion. Collagen and PRP provided reasonable socket preservation as simple and inexpensiveoptions as compared to other materials.